Prophage: agent provocateur? - Erdogdu, Berna; Dokuz, Senanur; Sarigode, Elif; Karabasoglu, Caner; Ozbek, Tulin (SPRINGER HEIDELBERG, 2026)
Bacteriophages make important contributions to the evolution, pathogenesis, and general biology of host bacteria. Throughout their life cycle, temperate bacteriophages form stable relationships with their hosts, which contribute to the evolution and biology of phages, rather than simply explaining a passive process in which hosts are affected. Although lytic phages have been extensively studied in the literature, temperate phages have been excluded due to some traditional perspectives. In this review article we discuss the lysogenic life cycle of phages and the essential points necessary to understand this cycle in detail. The lysogenic cycle has been evaluated from three perspectives; phage, bacteria and human. In some cases, temperate phages exhibit symbiotic relationships with bacteria, while in others, their hostile behavior causes uncertainty as to whether they are on the side of humans or bacteria. Our perspective challenges the classical interpretation by suggesting that prophages can act as provocateur agent, offering advantages while also harboring destructive potential, thereby playing a complex role against bacteria and potentially exerting intricate effects on human health.
Keywords: Bacteriophages; Temperate phages; Lysogenic conversion; Active lysogeny; Phage genomics; Lysogeny mechanistic diversity; ESCHERICHIA-COLI; EVOLUTIONARY RELATIONSHIPS; BACTERIOPHAGE; RESISTANCE; ADAPTATION; VIRULENCE; LYSOGENY; SIGNAL; PHAGES; LYSIS; Microbiology